Liderazgo directivo predictor de la gestión de la convivencia escolar en instituciones educativas públicas del nivel secundario de la ciudad de Requena 2024 - Sanchez Babilonia, Juliana (2025)
The purpose of this research was to evaluate the level of accuracy in predicting leadership in relation to the management of school coexistence in public secondary education institutions in the town of Requena. A study was conducted using an ex post facto, cross-sectional, and contemporary approach. The sample consisted of 124 teachers from these institutions. A contrast analysis was performed to validate the general hypothesis; it can be stated that the predictor: intervention skill is significant, while communication and organization and relational skill are not significant. Regarding the management of school coexistence, 50% of teachers perceive that the dimensions of pedagogical leadership are always carried out. On the other hand, 74.2% of educators consider that school coexistence management is almost always carried out. Most leadership dimensions are linked to the dimensions of school management (p < 0.05) in public secondary education institutions in the district of Requena 2024.